2014
DOI: 10.3762/bjoc.10.267
|View full text |Cite
|
Sign up to set email alerts
|

An integrated photocatalytic/enzymatic system for the reduction of CO2 to methanol in bioglycerol–water

Abstract: SummaryA hybrid enzymatic/photocatalytic approach for the conversion of CO2 into methanol is described. For the approach discussed here, the production of one mol of CH3OH from CO2 requires three enzymes and the consumption of three mol of NADH. Regeneration of the cofactor NADH from NAD+ was achieved by using visible-light-active, heterogeneous, TiO2-based photocatalysts. The efficiency of the regeneration process is enhanced by using a Rh(III)-complex for facilitating the electron and hydride transfer from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 26 publications
2
59
0
1
Order By: Relevance
“…Most commonly, CO 2 reduction has been explored with the aim of producing formate or alkanes/alcohols, although NAD þ reduction to NADH is frequently attempted where NAD-dependent enzymes can support reductive reactions [22][23][24]; Vincent and co-workers [25] have also demonstrated that the coimmobilization of hydrogenase and NAD þ -reducing proteins onto conductive particles can facilitate H 2 -driven NADH production. Recent research has also explored the possibility of reducing dinitrogen (N 2 ) to an important chemical commodity, ammonia (NH 3 ), while simultaneously producing electrical energy [26].…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, CO 2 reduction has been explored with the aim of producing formate or alkanes/alcohols, although NAD þ reduction to NADH is frequently attempted where NAD-dependent enzymes can support reductive reactions [22][23][24]; Vincent and co-workers [25] have also demonstrated that the coimmobilization of hydrogenase and NAD þ -reducing proteins onto conductive particles can facilitate H 2 -driven NADH production. Recent research has also explored the possibility of reducing dinitrogen (N 2 ) to an important chemical commodity, ammonia (NH 3 ), while simultaneously producing electrical energy [26].…”
Section: Introductionmentioning
confidence: 99%
“…To provide the possibility for practical application, a hybrid enzymatic/photocatalytic approach for efficient converting CO2 into methanol was recently proposed [35]. The proposed approach includes two processes: the enzymatic transformation of CO2 to Scheme 2.…”
Section: Conversion Of Co2 To Formic Acid/formatementioning
confidence: 99%
“…It has been shown that under photocatalytic conditions and in the absence of the rhodium catalyst, the formation of complex product mixtures is possible [110]. Steckhan and coworkers identified the reduced nicotinamide cofactor product during photoredox catalysis with [Ru(bpy) 3 ] 2+ as the chromophore in the absence of a rhodium catalyst as the dimeric (NAD) 2 species [73].…”
Section: Nad(p)h Formation Using the [(Bpy)rh(cp*)x] N+ Motivementioning
confidence: 99%
“…It has been shown that under photocatalytic conditions and in the absence of the rhodium catalyst, the formation of complex product mixtures is possible [110]. Steckhan and coworkers Identically to the photocatalytic generation of hydrogen, the catalytically active rhodium complex is most likely formed via the fast disproportionation of the intermediate Rh II species [33,37].…”
Section: Nad(p)h Formation Using the [(Bpy)rh(cp*)x] N+ Motivementioning
confidence: 99%
See 1 more Smart Citation